A first‐in‐human phase I, multicenter, open‐label, dose‐escalation study of the oral RAF/VEGFR‐2 inhibitor (RAF265) in locally advanced or metastatic melanoma independent from BRAF mutation status. (18th July 2017) - Izar, Benjamin; Sharfman, William; Hodi, F. Stephen; Lawrence, Donald; Flaherty, Keith T.; Amaravadi, Ravi; Kim, Kevin B.; Puzanov, Igor; Sosman, Jeffrey; Dummer, Reinhard; Goldinger, Simone M.; Lam, Lyhping; et al.
Abstract: To establish the maximum tolerated dose (MTD), dose‐limiting toxicities (DLT), safety profile, and anti‐tumor efficacy of RAF265. We conducted a multicenter, open‐label, phase‐I, dose‐escalation trial of RAF265, an orally available RAF kinase/VEGFR‐2 inhibitor, in patients with advanced or metastatic melanoma. Pharmacokinetic (PK) analysis, pharmacodynamics (PD) and tumor response assessment were conducted. We evaluated metabolic tumor response by 18[F]‐fluorodeoxyglucose‐positron‐emission tomography (FDG‐PET), tissue biomarkers using immunohistochemistry (IHC), and modulators of angiogenesis. RAF265 has a serum half‐life of approximately 200 h. The MTD was 48 mg once daily given continuously. Among 77 patients, most common treatment‐related adverse effects were fatigue (52%), diarrhea (34%), weight loss (31%) and vitreous floaters (27%). Eight of 66 evaluable patients (12.1%) had an objective response, including seven partial and one complete response. Responses occurred in BRAF‐mutant and BRAF wild‐type (WT) patients. Twelve of 58 (20.7%) evaluable patients had a partial metabolic response. On‐treatment versus pretreatment IHC staining in 23 patients showed dose‐dependent p‐ERK inhibition. We observed a significant temporal increase in placental growth factor levels and decrease in soluble vascular endothelial growth factor receptor 2 (sVEGFR‐2) levels in all dose levels. RAF265 is an oral RAF/VEGFR‐2 inhibitor that produced antitumor responses, metabolic responses, and modulated angiogenic growth factor levels. Antitumor activity occurred in patients with BRAF‐mutant and BRAF‐WT disease. Despite low activity at tolerable doses, this study provides a framework for the development of pan‐RAF inhibitors and modulators of angiogenesis for the treatment of melanoma. Abstract : Metabolic responses based on FDG‐PET assessment. PMR partial metabolic response, SMD stable metabolic disease, PMD progressive metabolic disease. *indicates patients with PMD as defined inMethods .